Räumlich differenziert, zeitlich verschiedenartig: Lebenszyklen als Zugang zu einem besseren Verständnis von Suburbia in deutschen Großstadtregionen - Hesse, Markus; Polívka, Jan; Reicher, Christa (Raumforschung und Raumordnung | Spatial Research and Planning, 2018)
This paper takes a spatially differentiated and temporally variegated perspective on suburban areas. It proposes a conceptual framework for studying the temporal variation and related trajectories of the subject matter, with suburban lifecycles being the key to our analysis. In empirical terms, the paper summarises the findings of research undertaken in 12 selected locales of four major metropolitan regions in Germany. Against the background of assessing the broader socioeconomic development of these regions, detailed local case studies have been conducted in order to reconstruct past and current development trajectories. Our analyses detected particular life cycles (and related segments) in the study areas, based on age and social composition, the physical conditions of the built environment and broader developments in the real-estate market. The different cycles include, in most cases, growth, maturity, transition and resilience, and they are also discussed in terms of their relevance for strategies responding to recent changes.
Keywords: Suburban life cycles; Development trajectories; Place-making; German city regions